Community-Based Development of Community Religious Behavior Through the Tegging Tourism Object of Suban District Rejang Lebong - Idris, Muhammad; Indrawari, Karliana; Al Fanzhari, Achmad Syauqi; Sadea, Koriatul (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The religious behavior of some young people often gets attention from society, such as the occurrence of brawls, leaving prayers, promiscuity, suicide and other negative behaviors. This service aims to find out: coaching, materials, constraints and follow-up community-based religious behavior development through Suban Cliff Tour, Rejang Lebong Regency. The subjects and objects of guidance in this activity are the community, namely several PAI Study Program students who are members of YBM BRI STAIN Curup. This service uses a model of counseling and mentoring with lectures, discussions and halaqa methods. Data in this service is taken based on the results of the service in the form of observations and interviews.  Results of dedication: first, the formation of religious behavior through several stages. Second, the material of guidance includes the material of creed, worship and morals. Third, the obstacles encountered are financing, time and student assignments, the fourth follow-up of this activity is to provide independent tasks to assisted participants and related to the ability to read the Quran, there must be significant efforts from participants. Conclusion; This service is carried out in the form of fostering the religious behavior of the younger generation who are members of the YBMI BRI STAIN Curup community. Guidance in the form of assistance and counseling to fostered objects related to religious material which includes creed, worship and morals.